2018
DOI: 10.20944/preprints201803.0101.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Drying Methods on Some Nutritional and Volatile Components of Bombay Red Onion <em>(Allium cepal L.)</em>

Abstract: Onion (Allium cepa L.) is a strong-flavoured vegetable consumed in different ways and its distinctive flavor or simply pungency. Onion has also important natural compounds effective for medical functions. Its importance is directly related with high content of high organosulphur compounds. Shelf life of fresh onion bulb is short enough due to the presence of high moisture content where postharvest loss of onion bulb reaches up to 50% in the production season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…Moreover, the polyphenol content of fresh onion was shown to be 1,220 mg/100 g DM. When compare with those reported in literature as 28 mg/100 g DM (Arslan & Özcan, 2010), 185.65 mg/100 g DM (Demissew et al., 2018), and 1366.31 ± 14.15 mg/100 g DM (Djiogue et al., 2018), it is noticed that the TPC of fresh onion is highly variety and production areas dependent. The TPC of the fresh onion in this study is closer to the value of Djiogue et al.…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…Moreover, the polyphenol content of fresh onion was shown to be 1,220 mg/100 g DM. When compare with those reported in literature as 28 mg/100 g DM (Arslan & Özcan, 2010), 185.65 mg/100 g DM (Demissew et al., 2018), and 1366.31 ± 14.15 mg/100 g DM (Djiogue et al., 2018), it is noticed that the TPC of fresh onion is highly variety and production areas dependent. The TPC of the fresh onion in this study is closer to the value of Djiogue et al.…”
Section: Resultssupporting
confidence: 49%
“…Some researchers have reported the decrease in TPC (Djiogue et al., 2018; Heras‐Ramírez et al., 2012; López‐Vidaña, Figueroa, Cortés, Rojano, & Ocaña, 2017; Vega‐Gálvez et al., 2012), whereas some of them have observed an increase in TPC (Arslan & Özcan, 2010; Lee et al., 2016). On the other hand, others authors have also indicated an increase followed by a decrease in TPC (Larrauri, Rupérez, & Saura‐Calixto, 1997; Raja et al., 2017), and others have observed no significant change of TPC during onion flake drying at 50 °C (Demissew, Meresa, & Temesgen, 2018). However, the effect of drying on total polyphenols behavior would depend on the class of polyphenols (Madrau et al., 2009).…”
Section: Resultsmentioning
confidence: 96%
“…al. [4], focus on nutritional value and volatile components of red onions. In there study implementing sliced onions to ready for ingredients for the purpose.…”
Section: Vamentioning
confidence: 99%